Does Cattle Grazing and Baling of Corn Residue Increase Water Erosion?. Issue 1 (22nd January 2016) - Blanco-Canqui, Humberto; Stalker, Aaron L.; Rasby, Rick; Shaver, Tim M.; Drewnoski, Mary E.; van Donk, Simon; Kibet, Leonard
Abstract : Core Ideas: Water erosion did not increase after one season of grazing, but it significantly increased after seven seasons of grazing. Baling increased water erosion and its effects were larger than grazing. Water erosion increased as residue cover decreased. A better understanding of the implications of corn ( Zea mays L.) residue grazing and baling on soil and environmental quality is needed to develop sustainable integrated crop–livestock production systems. We studied how corn residue grazing and baling impacted water erosion in a rainfed and an irrigated site in Nebraska after one and seven grazing seasons, respectively. Treatments were grazing (4.4 animal unit mo [AUM] ha −1 ), baling, and control (no residue removal) in triplicate at the rainfed site on a Yutan silty clay loam (6% slope) and light grazing (2.5 AUM ha −1 ), heavy grazing (5 AUM ha −1 ), baling, and control in duplicate at the irrigated site on Duroc loam and Satanta loam (5.3% slope). We measured erosion under simulated rainfall for 30 min at an intensity of 6.3 ± 1.2 cm h −1 . Erosion did not increase after one season of grazing at the rainfed site, but it significantly increased after seven seasons of grazing at the irrigated site. At this site, both heavy and light grazing increased runoff by 3.3 mm and sediment loss by 0.26 Mg ha −1 . Baling had larger effects on water erosion than grazing. Across both sites, baling reduced time to runoff start by 14 min and increased runoff by 13 mm and sediment loss by 2.7 Mg ha −1 . While grazing after seven seasons increased nutrient loss, baling caused larger nutrient losses at both sites. Overall, grazing caused runoff losses of sediment, C, and nutrients in the long term, but baling consistently increased such losses in both short and long term.